Evaluation of Assam rice (Oryza sativa) genotypes for nitrogen use efficiency - DAS, SHANTANU; BORAH, PRAKASH; SARMA, DEBOJIT; DAS, S S; BARUA, N S; BABU, SUBHASH (The Indian Journal of Agricultural Sciences, 2021)
We assessed genetic diversity in 26 rice genotypes including 21 landraces and five improved varieties grown in three different nitrogen doses, viz. 0, 40, and 60 kg/ha during kharif 2014-15, and identified superior nitrogen use efficient genotypes for lowland rice ecosystem. The presence of significant genotypic differences was registered for 12 quantitative traits of nitrogen use efficiency, grain yield, and its related traits. Mahalanobis distance-based clustering grouped the genotypes into seven clusters. The maximum contribution towards divergence was due to flag leaf area followed by physiological nitrogen use efficiency and grain yield/plant. Principal component analysis performed on the 12 quantitative traits revealed that the first four principal components accounted for 83.57% variance among the genotypes. Grain yield/plant (0.43), nitrogen utilization efficiency (0.39), and nitrogen harvest index (0.37) accounted most for principal component 1. The genotypes namely Lothabor, Betguti Sali, and Luhasali were found to be suitable for the lowland rice ecosystem.